Evaluating the Effectiveness of Agricultural and Forestry Policies in Achieving Environmental Goals Through Policy Documents - Balode Lauma; Blumberga Dagnija (Environmental and Climate Technologies, 2023)
To achieve the climate targets set by 2030 and become climate neutral by 2050, each Member State must develop a National Energy and Climate Plan (hereinafter NECP) containing practical and effective measures to achieve the targets. The research sought a connection between the measures or action lines in the Latvian NECP related to agriculture and forestry, the European Green Deal goals and related strategies. The effectiveness of the agricultural and forestry measures defined in the Latvian NECP was evaluated by defining appropriate indicators, an expert survey and a composite sustainability index. The results show that the effectiveness of agricultural and forestry measures is most influenced by quality, financing, and specificity factors. The lowest-scoring measures were specific measures whose impacts cannot be measured and are not explicitly mentioned in the European Green Deal. Therefore, the description of the measures should be more detailed, with specific activities, indicators to be achieved, and amounts and funding sources planned for each activity.